Development of a CPM Device for Elbow Rehabilitation - Gonzales, Adriel; Furukawa, Roberto (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
This project presents the development of a Continuous Passive Motion (CPM) device for elbow rehabilitation, focusing on flexion-extension and pronation-supination movements. The need for such a device arises from the increasing number of patients requiring effective rehabilitation following elbow injuries or surgeries. The CPM device aims to facilitate the recovery process by providing controlled and precise movements that enhance joint mobility, reduce pain, and promote healing. The device is designed as a comprehensive mechatronic system, encompassing three primary domains: mechanical, electronic, and control.One innovative aspect of this project is the proposal to integrate a mobile application for remote monitoring and control. This application, leveraging the device’s electronic components, will allow real-time feedback and adjustments to the therapy regimen based on patient progress. This feature aims to enhance patient engagement and provide healthcare professionals with valuable data for optimizing rehabilitation protocols. These domains are thoroughly explored throughout this paper, highlighting the interdisciplinary approach and the potential impact of the device on improving rehabilitation outcomes.